2004
DOI: 10.1109/lpt.2003.820099
|View full text |Cite
|
Sign up to set email alerts
|

Bragg Grating-Based Fiber-Optic Laser Probe for Temperature Sensing

Abstract: Abstract-A novel Bragg grating-based fiber-optic laser probe for temperature sensing using erbium-doped fiber as the active gain medium is reported. The combination of a chirped grating and a normal grating was used to form the laser cavity to achieve temperature-tunable laser action over a wide measurement range. The laser probe used a metal sheath to enhance its mechanical strength and contain the normal grating at the sensing point. The temperature dependence of the wavelength of the laser probe gives a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Laser are employed for variety of applications such as bar code scanners [5], sensing [6,7], heat treatment [8-10], surface engineering [11,12], and machining of various materials [2]. In the medical field, they have been used for various surgeries in the fields including dentistry, opthalmology, and orthopedics.…”
Section: Laser Machiningmentioning
confidence: 99%
“…Laser are employed for variety of applications such as bar code scanners [5], sensing [6,7], heat treatment [8-10], surface engineering [11,12], and machining of various materials [2]. In the medical field, they have been used for various surgeries in the fields including dentistry, opthalmology, and orthopedics.…”
Section: Laser Machiningmentioning
confidence: 99%
“…Murphy et al [8] have reported a silica fiber extrinsic Fabry-Pérot (FP) strain sensor to measure temperatures up to 975 • C. Alavie et al [9] have reported a serial multiplexed sensor system where each laser cavity was formed using an FBG and a broadband mirror, measuring the temperature from 20 • C to 160 • C. Kaddu et al [10] have reported multiplexed optical fiber FP sensor systems to measure temperature and strain over the ranges from 20 • C to 70 • C and from 0 to 400 µε, respectively. Peng et al [11] have reported an FBGbased temperature sensor system using a fiber laser to measure temperature over the range from 0 to 40 • C. A Raman fiber laser probe has also been developed [12] for long-distance remote temperature sensing applications, typically reported for use over the temperature range from 30 to 100 • C. Recently, fiber laser-based sensor systems have been developed to measure temperatures up to 500 • C in a single cavity configuration using a chirped FBG (CFBG) and a normal FBG in [13] and [14]. Additionally, some of the commercial manufacturing technologies are also available for temperature measurement applications [15], [16].…”
Section: A Parallel Multiplexed Temperature Sensor Systemmentioning
confidence: 99%
“…Commercially, available fiber optic temperature sensors often use a semiconductor-chip, which has an absorption edge that moves with the temperature [5,6]. Other sensors utilize Bragg gratings [7][8][9] or the temperature-dependent fluorescence intensity of certain materials [10] to measure the temperature. Another way is to analyze the Raman scattering in a glass fiber [11] or to analyze the temperature with a Fabry-Pérot interferometer (FPI) [12,13] or with a Mach-Zehnder interferometer [14] integrated into an optic fiber.…”
Section: Introductionmentioning
confidence: 99%